Temperature sensor module (TSM) for detecting groundwater flow velocity and direction - Alexander Michalski; Norbert Klitzsch (PANGAEA, 2019)
Here, we present the first application of the temperature sensor module (TSM) for detecting groundwater flow velocity and direction. The TSM maps the horizontal temperature distribution around a borehole heat exchanger (BHE). Groundwater flow distorts this temperature distribution. Thus, flow velocity and direction can be inferred from the measured temperatures. As modular systems, TSMs can be attached to BHE at any depth of interest. For the studied BHE, the depths of interest are at 82 m and at 94 m, where we installed TSMs. We recorded TSM data for two weeks before and during the operation of the BHE. After simulating the working fluid temperature in the depths of interest, we model the horizontal temperature distributions using the working fluid temperatures as input. We use the latter simulations for inferring groundwater flow by minimizing the root mean square error between measured and simulated temperatures. We obtain a groundwater flow of (0.4 ± 0.1) m per day in NW direction and groundwater flow below the detection limit of 0.01 m to 0.02 m per day in 82 m and 94 m depth, respectively. The results agree with the groundwater flow obtained by an optical method. The datasets are split in 4 files. 2 files include the temperature data and magnetic fieldsensor data for one TSM in one depth (82 m and 94 m), respectively. In each file temperature data for 24 sensors are stored( plus magnetic field sensor as 25 th in outer ring files). each 8 sensors correspondes to one sensor level of a TSM. Example: in file "*82m*inner*.txt" sensor 1-8 are the first level, 9-14 are second level and 15 - 24 are third level of inner rings. in file "*82m*outer*.txt" the same for sensors on the TSM surface. + the magnetic field sesnor as 25th sensor.
Supplement to: Michalski, A; Klitzsch, N (2019): First field application of temperature sensor modules for groundwater flow detection near borehole heat exchanger. Geothermal Energy, 7(1), https://doi.org/10.1186/s40517-019-0152-5